2016
DOI: 10.1113/ep085790
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic function of TRPV4 ion channels in the central nervous system

Abstract: TRPV4 ion channels are osmo-mechano-TRP channels with pleiotropic function and expression in many different types of tissues and cells. They have also been found involved in pain and inflammation. Studies have focused on the role of TRPV4 in peripheral sensory neurons, but its expression and function in central nervous glial cells and neurons has also been documented. In this overview, based on the senior author’s lecture at the recent physiology meeting in Dublin, we concisely review evidence of TRPV4 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…a search for ''TRPV4 pain'' generated 185 references out of a total of 1085 references for ''TRPV4''. Primary sensory neurons with TRPV4 expression include pain-sensing neurons in the DRG [8,255,256] and TG [257,258] [ 94,259], most recently also satellite cells in sensory ganglia [260], in the CNS for pain transmission in astrocytes [261], microglial cells [262], and neurons [263,264,265]. Outside the nervous system, TRPV4 has been found in innervated cells such as prominently in chondrocytes [266], vascular endothelia [267], and innervated epithelia such as skin keratinocytes [129,268], airway epithelial cells [26,269,270], colonic epithelia [271], and odontoblasts [272].…”
Section: Trpv4 Functions As a Pain-trp And An Itch-trpmentioning
confidence: 99%
“…a search for ''TRPV4 pain'' generated 185 references out of a total of 1085 references for ''TRPV4''. Primary sensory neurons with TRPV4 expression include pain-sensing neurons in the DRG [8,255,256] and TG [257,258] [ 94,259], most recently also satellite cells in sensory ganglia [260], in the CNS for pain transmission in astrocytes [261], microglial cells [262], and neurons [263,264,265]. Outside the nervous system, TRPV4 has been found in innervated cells such as prominently in chondrocytes [266], vascular endothelia [267], and innervated epithelia such as skin keratinocytes [129,268], airway epithelial cells [26,269,270], colonic epithelia [271], and odontoblasts [272].…”
Section: Trpv4 Functions As a Pain-trp And An Itch-trpmentioning
confidence: 99%
“…We demonstrated that intravascular pressure‐evoked increases in astrocyte Ca 2+ are partly mediated via TRPV4 channel activation (Kim et al, ). TRPV4 are Ca 2+ permeable nonselective cation channels (Plant & Strotmann, ) involved in numerous functions including, systemic tonicity, mechanosensation, pain, inflammation, and vascular tone (Earley et al, ; Hill‐Eubanks, Gonzales, Sonkusare, & Nelson, ; Kanju & Liedtke, ; Plant & Strotmann, ; Ryskamp, Iuso, & Krizaj, ; Vriens, Janssens, Prenen, Nilius, & Wondergem, ). TRPV4 channels expressed in the vasculature serve as molecular detectors and transducers of arteriole myogenic responses (e.g., mechanical stress; Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of TRPV4 in mammals is wide-spread. It is expressed in the central and peripheral nervous system 15 , noticeably in tissues involved in volume regulation and osmosensing such as the circumventricular organs, the vascular endothelium and the kidney 12 , 16 , 17 . In an earlier study expression of TRPV4 in the kidney has been reported to be restricted to the distal part of the renal nephron system, which is constitutively or conditionally water–impermeable 18 , thereby supporting its osmoregulatory role 17 .…”
Section: Introductionmentioning
confidence: 99%